Evolutionary parasitology the integrated study of infections, immunology, ecology, and genetics - Schmid-Hempel, Paul. (Oxford : Oxford University Press, 2011)
Parasites are among the most serious threats for any organism. This book brings together the knowledge from different fields and traces the basic ecological and evolutionary principles behind the eternal and momentous struggle between hosts and their parasites and how we understand it today.
Includes bibliographical references and index.
Description based on print version record.
Keywords: Parasitism